Integrated decentralizes food system governance at the district level - Ouch, Mara; Sithirith, Mak; De Silva, Sanjiv; Sok, Sao (WorldFish, 2024)
The Tonle Sap Lake and Mekong Delta drive Cambodia’s food production, but climate change and infrastructure disrupt hydrology, threatening food security. Natural resource governance, including FWUCs, CFis, CFRs, ACs, and CBETs, remains decentralized and siloed, causing conflicts among fishers, farmers, and sectors, undermining sustainability in Beung Sneh and Beung Ream. Cambodia’s 2019 decree promotes integrated governance, but district-level frameworks lack technical, financial, and human resources. Strengthening governance requires adopting landscape approaches, forming District Technical Working Groups (DTWGs), building member capacities, and allocating national budgets. Lessons from Beung Sneh and Beung Ream pilots inform scaling efforts and national strategy integration.